Donne e tossicodipendenza. Quando la patologia è di altro genere… - Lacatena, Paola (Mission - Open Access, 2020)
The European Drug Report 2017: Trends and Developments, published by the Libson based European Monitoring Centre for Drugs and Drug Addiction (EMCDDA) reports that only 20% of patients who undergo treatment for drug addiction are female (a male-female ratio of 4:1). According to the EMCDDA, the reasons for this are varied and could include issues of access and appropriateness of service provision. Using data from two trials conducted within the Department of Pathological Addictions of the Local Health Service of Taranto, this article’s intent is to highlight the necessity of specific focusing in terms of health, rehabilitation programmes, and access to services for women drug consumers and addicts. Helping women addicts to become independent, making them aware of their own potential, offering them a real sense of self worth to value and defend, promoting the safeguarding of their own health; all these are essential elements of treatment and rehabilitation, for the prevention and limitation of any harm.